Kidney microbiota dysbiosis contributes to the development of hypertension - Xin-Yu Liu; Jing Li; Yamei Zhang; Luyun Fan; Yanli Xia; Yongyang Wu; Junru Chen; Xinyu Zhao; Qiannan Gao; Bing Xu; Chunlai Nie; Zhengyu Li; et al. (Gut Microbes)
Gut microbiota dysbiosis promotes metabolic syndromes (e.g., hypertension); however, the patterns that drive hypertensive pathology and could be targeted for therapeutic intervention are unclear. We hypothesized that gut microbes might translocate to the kidney to trigger hypertension. We aimed to uncover their method of colonization, and thereby how to maintain blood pressure homeostasis. Using combined approaches based on fluorescence in situ hybridization (FISH) and immunofluorescence staining, electron microscopy analysis, bacterial cultures, species identification, and RNA-sequencing-based meta-transcriptomics, we first demonstrated the presence of bacteria within the kidney of spontaneously hypertensive rats (SHRs) and its normotensive counterpart, Wistar-Kyoto rats (WKYs), and patients with hypertension. Translocated renal bacteria were coated with secretory IgA (sIgA) or remained dormant in the L-form. Klebsiella pneumoniae (K.pn) was identified in the kidneys of germ-free (GF) mice following intestinal transplantation, which suggested an influx of gut bacteria into the kidneys. Renal bacterial taxa and their function are associated with hypertension. Hypertensive hosts showed increased richness in the pathobionts of their kidneys, which were partly derived from the gastrointestinal tract. We also demonstrated the indispensable role of bacterial IgA proteases in the translocation of live microbes. Furthermore, Tartary buckwheat dietary intervention reduced blood pressure and modulated the core renal flora-host ecosystem to near-normal states. Taken together, the unique patterns of viable and dormant bacteria in the kidney provide insight into the pathogenesis of non-communicable chronic diseases and cardiometabolic diseases (e.g., hypertension), and may lead to potential novel microbiota-targeted dietary therapies.